Study on the Iodine 125 Uptake of H460 Lung Cancer Cell Line by Co-transfection with the Human Sodium/Iodide Symporter and the Human Thyroperoxidase - Wei LI; Jian TAN; Lei LONG (Chinese Journal of Lung Cancer, 2010)
Background and objective Lung cancer harms people’s health or even lives severely. Especially, the therapy of non-small cell lung cancer (NSCLC) has not been obviously improved for many years. The aim of this study is to transfer the human sodium/iodide symporter (hNIS) and the human thyroperoxidase (hTPO) genes into H460 lung cancer cell line, and to study the uptake ability of iodide after co-transfected hTPO and hNIS gene in cell lines. Methods Through cloning, recombination, packaging and amplifying, the recombinant adenosine virus (AdTPO) was constructed. Then the protein expression of AdTPO was tested by Western blot. After transfected hNIS gene into human lung cancer cell line H460 through liposome, stably expressing hNIS gene cell lines (hNIS-H460) selected by G418 antibiotics was determined as hNIS-H460 group. Using AdTPO, hTPO gene was transducted into hNIS-H460, as AdTPO-hNIS-H460 group. H460 cell without hNIS gene was applied as control group (H460). Then, we investigated the 125I uptake assay of the above cells. Results We were successful in co-transfecting hNIS and hTPO gene into human lung cell lines H460, and were obtained hNIS and hTPO gene lung cancer cell lines (hNIS-H460 and AdTPO-hNIS-H460). In AdTPO-hNIS-H460, hNIS-H460 and H460, the uptake ability of 125I was (59 637.67±1 281.13), (48 622.17±2 242.28) and (1 440.17±372.86) counts•min-1. The uptake ability of 125I was 41 fold higher in AdTPO-hNIS-H460 than in blank control H460 (P<0.01), and 34 fold higher in hNIS-460 than in blank control H460 (P<0.01), and 1.2 fold higher in AdTPO-hNIS-H460 than in hNIS-H460 (P<0.01). Conclusion The uptake ability of 125I could increase by co-transfected hNIS and hTPO genes into human lung cancer cell lines H460.